Answer:
x = 7
Explanation:
How to solve your question
Your question is 13 + 3 − 8x + 6 = 1 − 5x
13 +3 - 8x + 6 = 1 - 5x
13 + 3 − 8x + 6 = 1 − 5x
Solve
Add the numbers
13 + 3 − 8x + 6 = 1 − 5x
22 − 8x = 1 − 5x
Rearrange terms
22 − 8x = 1 − 5x
−8x + 22 = 1 − 5x
Subtract 22 from both sides of the equation
−8x + 22 −22 = −5x + 1 − 22
Simplify
Subtract the numbers
−8x = -5x + 1 -22
-8x = -5x -21
Add 5x to both sides of the equation
-8x + 5x = -5x -21 + 5x
Simplify
Combine like terms
-3x = -21
Divide both sides of the equation by the same term
(-3x)/3 = (-21)/3
Simplify
Cancel terms that are in both the numerator and denominator
x = (-21)/(-3)
Divide the numbers
x = 7